Temporomandibular Disorders (TMD) in Edentulous Patients: A Review and Proposed Classification (Dr. Bader’s Classification). - Bader K AlZarea (Journal of Clinical and Diagnostic Research, 2015)
Temporomandibular disorders (TMD) are a collective term given to a number of clinical problems that involve the masticatory musculature, the temporomandibular joints and associated structures, or both. Although the aetiology of TMD has not been fully understood, in general it is considered to be multifactorial. The signs and symptoms of TMD which present in patients with natural teeth may also occur in edentulous patients. These symptoms may appear in various combinations and degrees. TMD has attained a prominent role within the context of dental care due to its high prevalence. The present paper is a review of the current literature on TMD in edentulous patients; with an attempt to propose a classification for the same.